Penghapusan Sarana Prasarana Pendidikan - Setiyadi, Bradley; Ramadhan, Bintang; Ulfa, Marya; Rosdiati, Rida; Putri, Tias Hersalainda (Jurnal Ilmiah Dikdaya, 2024)
Educational facilities and infrastructure are vital elements in the education system, regulated by the National Education System Law No. 20 of 2003. The removal of educational facilities and infrastructure becomes a crucial activity to free educational institutions from non-functional assets. This article discusses the concepts, objectives, requirements, mechanisms, and methods of removing educational facilities and infrastructure. The concept of removing educational facilities and infrastructure encompasses the process of freeing assets considered non-functional for justifiable reasons. The primary objective of this removal is to prevent wasteful maintenance costs, free up space, and enhance the efficiency of inventory management. The method of removing educational facilities and infrastructure can be carried out through auctioning or disposal. Auctioning is directed towards items that still have economic value, while disposal is applied to items that are no longer saleable or lack economic value. This article employs a literature review method with a qualitative descriptive approach to analyze the concepts and mechanisms of removal. Thus, this article provides an in-depth understanding of the removal of educational facilities and infrastructure, exploring the objectives, requirements, mechanisms, and methods necessary in the management of educational resources.